An investigation of seeming favoritism in public procurement. (12th December 2020) - Pi, Jiancai
Abstract: The existing literature holds that favoritism in public procurement is due to discrimination or corruption. In procurement, the government agency faces a tradeoff between the expected allocative efficiency and the expected rent paid to the contracting firm. When the government agency's efficiency gain is larger (resp. smaller) than its rent loss, it is optimal for the government agency to choose the contract with the low‐cost (resp. high‐cost) firm. The general public usually deems that the latter case implies that there exists favoritism in public procurement. We point out that such seeming favoritism is not favoritism in the true sense. There may be an over‐identification of favoritism in public procurement in the existing literature.